ELECTRIC POWER IN THE TASHKENT ECONOMIC REGION: TERRITORIAL LOCATION AND STAGES OF DEVELOPMENT - Toirova Z. S. (TARIXIY TADQIQOTLAR, 2026)
This article studies the stages of the formation and development of the electric power sector in the Tashkent economic region. The article covers the electrification processes carried out to meet the needs of industry and the population, the construction of new hydroelectric power plants and GRES, the modernization of existing capacities, and the expansion of energy networks based on historical sources. It analyzes how the development of electric power in the region has served not only the industry, but also the continuous growth of the living standards of the population. The various sources of energy production in the Tashkent economic region and their economic and social significance, as well as the share and role of hydroelectric power plants and GRES, are substantiated with step-by-step examples. The results obtained demonstrate the energy leadership potential of the Tashkent economic region throughout the republic.